1996
DOI: 10.1111/j.1365-2621.1996.tb10900.x
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐Induced Aggregation and Gelation of Whey Proteins

Abstract: Aggregation and gelation of whey proteins induced by a specific protease from Bacillus licheniformis was revealed by turbidimetry, size exclusion chromatography, dynamic light scattering and rheology. The microstructure of the gel was examined by transmission electron microscopy. During incubation of 12% whey protein isolate solutions at 40ЊC and pH 7, the major whey proteins were partly hydrolyzed and the solution gradually became turbid due to formation of aggregates of increasing size. The viscosity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 13 publications
2
62
0
Order By: Relevance
“…On the other hand, the structure of the proteins is altered during hydrolysis since buried hydrophobic groups are exposed and free to interact. It is proposed that noncovalent interactions, mainly electrostatic and hydrophobic, are major interacting forces since they promote aggregation and subsequent gel settings (Fuke et al, 1985, Otte et al, 1996, Otte et al, 1997, Jeewanthi et al, 2015. However, Kuipers et al (2005) concluded based on their findings that the aggregation is not a simple balance between repulsive electrostatic and attractive hydrophobic interactions, but much more complex.…”
Section: Gelling Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, the structure of the proteins is altered during hydrolysis since buried hydrophobic groups are exposed and free to interact. It is proposed that noncovalent interactions, mainly electrostatic and hydrophobic, are major interacting forces since they promote aggregation and subsequent gel settings (Fuke et al, 1985, Otte et al, 1996, Otte et al, 1997, Jeewanthi et al, 2015. However, Kuipers et al (2005) concluded based on their findings that the aggregation is not a simple balance between repulsive electrostatic and attractive hydrophobic interactions, but much more complex.…”
Section: Gelling Propertiesmentioning
confidence: 95%
“…However, Kuipers et al (2005) concluded based on their findings that the aggregation is not a simple balance between repulsive electrostatic and attractive hydrophobic interactions, but much more complex. Gelling properties are observed both with limited hydrolysis (Ju et al, 1995;Otte et al, 1996;Kuipers et al, 2005) and more extensive hydrolysis, DH > 15% (Doucet et al, 2001). …”
Section: Gelling Propertiesmentioning
confidence: 96%
“…The hydrolysis of WPI by BLP has been shown to lead to the formation of a soft gel with a particulate structure (Otte et al, 1996). The formation of enzyme-induced aggregates thus determines the gelation properties of WPI after hydrolysis (Otte et al, 1996).…”
Section: Peptide-peptide Interactionsmentioning
confidence: 99%
“…Hydrophobic interactions among peptides, with a molecular mass less than 2 kDa, were observed to be involved in the formation of aggregates that associated further to form a gel (Doucet, Otter, Gauthier, & Foegeding, 2003). Also, it has been shown that partial hydrolysis of WPI with a serine protease from Bacillus licheniformis (BLP) may lead to the formation of enzymeinduced aggregates that eventually form a gel (Otte, Ju, Faergemand, Lomholt, & Qvist, 1996). A similar type of aggregate is formed when b-lactoglobulin (b-lg), the most abundant protein in bovine whey, is hydrolysed with BLP (Otte et al, 1997), suggesting that b-lg is mainly responsible for the effects observed with WPI.…”
Section: Introductionmentioning
confidence: 96%
“…Under specific conditions, these aggregates can form gel networks, which have improved properties compared with the nonhydrolyzed protein. 4,5,10,11 In contrast to the formation of aggregates, peptides can also prevent aggregation. Peptides derived from milk or soy proteins were shown to have the ability to inhibit blood platelet aggregation.…”
Section: Introductionmentioning
confidence: 95%